KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK FRUIT LEATHER KENITU (Chrysophyllum cainito L.) DENGAN PENAMBAHAN CMC DAN KARAGENAN - Herlina Herlina; Maria Belgis; Lufi Wirantika (Faculty of Agricultural Technology, University of Jember, 2020)
Star apple is a seasonal local fruit that is commonly found in East Java, Indonesia. This fruit contains high fiber and antioxidants, however the utilization was not optimal specially at the harvest season, so it requires for further processing. Star fruit apple processing into fruit leather would expected to resolve this problem. Plasticity is an important parameter in fruit leather quality which can be influenced by binding agent, sugar, and acid composition. Therefore, the aim of this study was to determine the best concentration of binding agent that can produce star apple fruit leathers with good characteristics and preferred by consumers. The concentration of CMC and carrageenan used in this study were 0.1%; 0.3%; 0.5%. Physicochemical data were analyzed by ANOVA (α = 5%) and DMRT, while preference were analyzed using Chi-square test (α = 5%). The best treatment determination was using scoring analysis. The result showed that 0.3% carrageenan was the best treatment to produce star apple fruit leather with 54.48 lightness; 348 g/ 2 mm texture; 17.99 KPa tensile strength; 9.03% elongation; 2.68% syneresis; 22.49% water content; and 6.11% crude fiber content. While the color, aroma, texture, taste, and overall preference were as follows 73.33%; 63.33%; 73.33%; 60%; and 66.67% respectively. Keywords: CMC, carrageenan, fruit leather, star apple